Why Brennan and Buchanan are wrong (after all) - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2007)
In their book The Power to Tax, Brennan and Buchanan have pointed to a central weakness of the traditional theory of public finance and especially of the theory of optimal taxation: This approach overlooked the problem of governmental power and the tendency of this power to be abused. It was important to demonstrate how grossly misleading the optimal taxation theory appears to be once the problem of power is considered. Nevertheless, Brennan and Buchanan's suggestions for constitutional rules are no less misleading, after all. Technically speaking, the public-policy implications of their approach are only valid under extremely unrealistic assumptions. What is worse: Shifting these assumptions somewhat closer to reality does not just reduce the extent to which the public-policy implications of their approach are true but rather turns them completely upside down. Hence, Barry Weingast's (1993, p. 287) fundamental trade off, according to which a 'government strong enough to protect property rights is also strong enough to confiscate the wealth of its citizens', remains unsolved.
Keywords: H11; H21; H26; D61; 330; public choice; optimal taxation; Leviathan theory; elasticity of tax bases; constitutional economics; Leviathan-Modell; Optimale Besteuerung; Public Choice; Verfassungsökonomik; Theorie